How will oil palm expansion affect to butterflies diversity in Jambi, Indonesia?. Issue 1 (February 2020) - Panjaitan, R; Buchori, D; Peggie, D; Harahap, I S; Drescher, J; Scheu, S; Hidayat, P
Abstract: The convertion of forest functions to oil palm plantations has an impact on biodiversity. One of the impacts of biodiversity may affect the butterflies diversity. This research was conducted in one of the oil palm areas in PT. Humusindo in Jambi. The purpose of this study were to determine the diversity and active time of butterflies in oil palm plantations of PT. Humusindo Jambi. The study was conducted for 2 months. Sampling method used for this research were scan sampling in the oil palm plantation area by capturing using insect nets. Butterflies are captured using insect nets then counted, marked (to avoid repeated calculations) and released again. Observation separated per one hour starting at 08.00 am to 04.59 pm. The results showed the highest diversity index of butterflies found was at 13.00-13.59 (H'=2.39) with total species number was 34 species. Overall, the butterfly diversity index found was relatively low (H'=1.78) with total species number was 54 species. The most dominant butterfly species found at each time of observation was Yptima praenubila . The conservation status of all species found were common species (there is no endemic species) and least concern in the conservation status.